2009
DOI: 10.1682/jrrd.2008.09.0113
|View full text |Cite
|
Sign up to set email alerts
|

Infectious complications in OIF/OEF veterans with traumatic brain injury

Abstract: Abstract-Of veterans from the U.S. Global War on Terrorism who have sought care in the Department of Veterans Affairs, approximately 12% have an infectious disease diagnosis. Infections in those veterans with traumatic brain injury (TBI) include infections associated with blast injuries and burns, such as skin and soft tissue infections; infections as a result of retained bullet or shrapnel fragments; pulmonary infections resulting from lung injury, intubation, or resultant tracheostomy; hospital-acquired infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Studies have shown that 5% of deployment-related infections involve Candida spp [ 30 ], as well as representing the second-most common organism in positive blood cultures in a population of veterans of the recent conflicts [ 31 ]. A civilian population of mostly blunt trauma with complicated postoperative courses had rates of Candida colonization and infection of 36.6% and 6.1%, respectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 5% of deployment-related infections involve Candida spp [ 30 ], as well as representing the second-most common organism in positive blood cultures in a population of veterans of the recent conflicts [ 31 ]. A civilian population of mostly blunt trauma with complicated postoperative courses had rates of Candida colonization and infection of 36.6% and 6.1%, respectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical health conditions evaluated included the most commonly reported conditions associated with mTBI in the ADSM and Veteran populations: pain, headaches, neurosensory, and neurological conditions [25]. Comparison of these conditions in ADSMs or Veterans with mTBI and no TBI was largely negative, however some specific conditions were found to be associated with mTBI.…”
Section: Physical Healthmentioning
confidence: 99%
“…Whilst there has been little systematic review of infections associated with these injuries, MDR A. baumannii has been described complicating CNS injuries in case reports [48][49][50].…”
Section: Initial Reports Combat-related Infections and Mortalitymentioning
confidence: 99%